Building a Scout Public Service Scale for first-year students in the faculties of physical education and sports sciences - Ilad Mohammed; Dr. Iqbal Abdul-hussein (الرياضة المعاصرة)
The importance of the study lies in building the Scout Public Service Scale for first-year students in the faculties of physical education and sports sciences.The research aimed to: Building the Scout public service standards for the first-year students of the faculties of physical education and sports sciences in the universities of the Middle Euphrates.